A fatal case of chlorfenapyr poisoning and a review of the literature. Issue 9 (September 2022) - Chien, Shih-Chun; Chien, Shih-Chao; Su, Yu-Jang
Background: Chlorfenapyr is a widely used pesticide and is classified as moderately hazardous to human health. Ingestion usually leads to mortality in humans. However, chlorfenapyr toxicity has a variable course and mechanism of action. Case presentation: We report the case of a 79-year-old female who ingested chlorfenapyr with the intent to commit suicide. The liquid was ingested 2 hours before she was brought to our emergency department. Gastric lavage was immediately performed. On admission, laboratory examinations revealed mildly elevated liver enzyme and creatinine kinase levels. Acute fever occurred on day 7; on day 8, the patient died of progressive respiratory distress and conscious disturbance. Chlorfenapyr toxicity leads to high rates of mortality (75%) and causes damage to the liver and the nervous system. Conclusions: It is necessary to observe patients with chlorfenapyr toxicity for 3 weeks because no significant abnormalities occur in the early phase. The onset of fever and deterioration of consciousness is a warning sign of a sudden fatal outcome. We review the literature and discuss neurologic and cardiopulmonary impairment in the clinical course of chlorfenapyr poisoning.